Biosynthesis and characterization of Cu-Se bimetallic nanoparticles: an effective approach as anticancer agents - Amany A. Hassabo; Basant A. Ali; Shaimaa A. Tawfik; Hossam E. Emam (Novel Research in Microbiology Journal)
Bimetallic nanoparticles (BNPs) have garnered a great interest rather than monometallic nanoparticles (NPs) in terms of biotechnological applications due to their enhanced properties. They have a growing interest as promising biomedical agents for drug delivery, antibacterial, and anticancer treatments due to their significant permeability and retention effects. Both of nano-size copper (Cu) and selenium (Se) exhibited a significant activity in biological treatment and drug delivery systems. Consequently, the present work aimed to focus on the novel biogenic synthesis of Cu-Se BNPs using cell-free extract of a marine bacterium, and studying their anticancer and antioxidant activities. Based on 16S rDNA sequencing, the isolated marine bacterium was identified Bacillus amyloliquefaciens by phylogenetic analysis. Biogenic synthesis of Cu-Se BNPs was optimized by studying the effect of some physiological factors such as reaction time, pH, and temperature. Based on the reaction conditions, the biologically synthesized Cu-Se NPs was obtained with different particle size that ranged from 15.7-106.0 nm. The spherical small sized (15.7 nm) bimetallic Cu-Se BNPs displayed anticancer activity against HepG2 and MDA cell lines, while the cell viability was reduced by 87 % and 81 %, respectively. The estimated IC50 values were 696.4 µg/ ml for HepG2 and 273.9 µg/ ml for MDA, while scavenging capacity (SC) of Cu-Se BNPs (SC50 = 305.3 µM) showed lower ability to 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) scavenging compared to ascorbic acid (SC50 = 95.9 µM).